Memahami Kebijakan Redaksional Rubrik Pendidikan di Surat Kabar Harian Solopos - Wulan, Sri (Jurnal The Messenger, 2016)
This study aims to understand how the framing of news is created in the education section of daily newspapers SOLOPOS. The main theory used in this research is the analysis of Todd Gitlin framing. With frames, journalist processing a wide range of information available to the pack in such a way in certain cognitive categories and presented to the audience. The methodology used is qualitative descriptive and analytical approach to framing using Todd Gitlin. This research was conducted at PT. AKSARA SOLOPOS Jl. Adisucipto No. Solo 190 57 145, with two (2) of informants in accordance with the criteria of the study subjects. The object of research is selected Pawiyatan money news relating to the acceptance of new students high school / vocational equivalent which in its message has content related message new admissions in July 2014. It was concluded from this study, education rubric SOLOPOS daily newspapers in reporting the news focus close to Solo and the surrounding community. The existence of sub-sections that are inserted every day to differentiate with other newspapers.
Keywords: Rubrik Pendidikan; Framing; Berita Pawiyatan